Comparative description of humeral bones of Aeneolitic (3500-2400 B.C.) and recent deer (Cervus elaphus L.) - Mihelić, Damir (Array, 1999)
Humeral bones fragments of Vučedol site (Vukovar-Croatia) which originate from Vučedol, Baden and Kostolac culture (3.500-2.400 B.C.) were studied. Bone fragment of red deer (Cervus elaphus L.) presented more den10 % of total number of animal bones. Red der s humeral bones fragments from eneolitic period is bigger and rugger then recent red deer. In our researched we found out that humeral bone of eneolitic red deer showed increasing index while humeral bone of recent deer showed decreasing index.